Systemic- Processual Shared Leadership Model with reference to Team Variables in IT Industry in India - Dr. Alka Agnihotri (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The team characteristics under shared leadership are very important variables determining goal accomplishment by teams . There have been numerous studies on shared leadership and team characteristics . How do the team characteristics vary in content and importance and how do they impact functioning of team and are of relevance to goal achievement ? This paper is devoted to such interesting explorations like processual and systematic understanding of shared leadership in general and it’s team characteristic in particular. In this regard, attempt is made to galvanise intellectual thought towards dynamic , processual and systematic study of variables related to team like team characteristics and shared leadership. The IT teams mostly handle changing , dynamic newer projects demanding readjustment of team variables . The sample included 300 team members for collection of responses with regard to the team characteristics like multidisciplinary contribution, technical complexity , distributed actions , reciprocal dependency , value to member expertise , decision making opportunity, member feedback , consensual working , synchronised plans . Based on correlational and variance analysis , effort has been made to explore if shared leadership can be looked upon as a system model with input , throughput and output sub-systems . The findings of this research study include not only how conglomeration of the team variables into a system with the input-throughput and output subsystem may happen but also the various components comprising these subsystems . Also these components’ findings about the input, throughput , output and feedback sub-systems were verified through discussions with the experts .